Tindig! Lesson Planning Challenges and Coping Strategies of Pre-service Teachers in a State University - Andrew A. Esteban; Eric DS. Ebro; Jericho A. Esguerra; Anna Mae M. Novicio (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
"Tindig" is a Filipino word that means "to rise" for pre – service teachers to be full fledge teacher in the future and a word that fits to capture their resilience, capability, and strength in overcoming challenges in order to be where they want to be. This study focuses on knowing what are the challenges that pre – service teachers are experiencing in making their lesson plan and their strategies in coping with the challenges in lesson planning. The researchers gathered data through a form of semi structured interview among BSED students. The results of the interview showed the difficulties that pre – service teachers experiences, that affects the quality of a lesson plan. These includes time famine, resource bottlenecking, cognitive overload, and spatial precarity. Nonetheless despite these challenges, the pre – service teachers showed resilience and were able to develop their tactics in addressing these challenges through coping strategies such as prioritizing essential task, allocating focused time intervals, practicing lesson plan deliberation and using applications, and seeking assistance and support from artificial intelligence.